Pelatihan Digital Assessment Berbasis Kahoot Dan Quizizz Dalam Pembelajaran Daring (Online) Untuk Guru SMP Muhammadiyah 61 Medan - Nasution, Dewi Kesuma; Manurung, Yayuk Hayulina; Arda, Mutia; Handayani, Susi (University of Muhammadiyah Sumatera Utara, 2022)
SMP Muhammadiyah 61 Tanjung Selamat is located on Jalan Perjuangan No. 18 Dusun II-B Tanjung Selamat, Sunggal sub-district, Deli Serdang Regency, North Sumatra Province. Tanjung Selamat Village is a suburb of Medan City as well as the border between Medan City and Deli Serdang Regency is a partner school of FKIP UMSU who was accompanied by lecturer facilitators in the Tanoto Foundation PINTAR program for the past 3 years where previously internship had been carried out using the Zoom application as an online learning medium during the pandemic by the previous team in April 2021 to October 2021 at SMP Muhamamdiyah 61 Medan. However, the improvement in teacher skills must also be in line with their ability to provide digital assessments to students, then digital assessment training through the Kahoot and Quiziz applications is the solution offered in this PKM activity. By being provided with digital assessment training based on Kahoot and Quizziz for the teachers of SMP Muhammadiyah 61 Medan, this program is expected to reduce the additional workload of teachers, such as correcting student assignments that are part of the assessment task, such as the final assessment of students not only depending on daily assessments, mid-assessments. semester and end of semester assessment. Quizziz and Kahoot as a form of digital assessment become authentic because the teacher can create contextual question materials and the teacher can insert images and videos from their own recordings into the Kahoot and Quizziz platforms.